2019
DOI: 10.3390/ijms20235891
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effect of Cadmium and Lead on Durum Wheat

Abstract: Cadmium (Cd) and lead (Pb) are two toxic heavy metals (HMs) whose presence in soil is generally low. However, industrial and agricultural activities in recent years have significantly raised their levels, causing progressive accumulations in plant edible tissues, and stimulating research in this field. Studies on toxic metals are commonly focused on a single metal, but toxic metals occur simultaneously. The understanding of the mechanisms of interaction between HMs during uptake is important to design agronomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 50 publications
3
26
0
Order By: Relevance
“…The nonenzymatic mechanisms of ROS detoxification may be activated; key nonenzymatic antioxidants comprise ascorbate, glutathione, flavonoids, vitamins, carotenoids, and alkaloids [52]. Aprile et al [54] suggested that wheat with low Cd and Pb in leaves has a high expression of the gene YSL2 which has a possible regulatory role in Cd compartmentalization in roots. The YSL2 is localized to vacuole membranes and can transport metal-NA complexes [55].…”
Section: Phytotoxicity and Detoxification Mechanism In Wheatmentioning
confidence: 99%
“…The nonenzymatic mechanisms of ROS detoxification may be activated; key nonenzymatic antioxidants comprise ascorbate, glutathione, flavonoids, vitamins, carotenoids, and alkaloids [52]. Aprile et al [54] suggested that wheat with low Cd and Pb in leaves has a high expression of the gene YSL2 which has a possible regulatory role in Cd compartmentalization in roots. The YSL2 is localized to vacuole membranes and can transport metal-NA complexes [55].…”
Section: Phytotoxicity and Detoxification Mechanism In Wheatmentioning
confidence: 99%
“…Its destructive role in the photosynthetic apparatus has been highlighted, where it reduces pigment contents [21]. Cadmium decreases carbon assimilation, reshaping the chloroplast ultra-structure and thylakoid composition [22][23][24]. Its strong affinity toward sulfate and the portentous component of enzymes leads to enzyme inhibition [25].…”
Section: Introductionmentioning
confidence: 99%
“…There is a crucial need to improve the production of wheat and barley for a growing population. However, environmental stresses such as salinity, drought, heat, freezing, heavy metal and even pathogen infections seriously threaten the growth and yield of wheat and barley under field conditions [5][6][7][8][9][10][11][12]. For instance, the majority of crops are highly sensitive to salinity, and the average yield of all important glycophytic crops decreased by 50%-80% at medium salinity conditions [5].…”
Section: Introductionmentioning
confidence: 99%
“…For heavy metal, cadmium (Cd) at low concentrations (0.3-0.8 mg kg −1 ) in soils could inhibit regular cell division, decrease photosynthesis and impair antioxidant enzyme activity [10,11]. In all major wheat-growing areas, lead (Pb) accumulation is generally accompanied by Cd pollution, seriously threatening crop yield and safety [12]. In acid soils, aluminum (Al) ions severely inhibit root growth and reduce the absorption of water and nutrients, resulting in crop yields [13].…”
Section: Introductionmentioning
confidence: 99%